2011
DOI: 10.1126/scitranslmed.3001571
|View full text |Cite
|
Sign up to set email alerts
|

5-Lipoxygenase Metabolite 4-HDHA Is a Mediator of the Antiangiogenic Effect of ω-3 Polyunsaturated Fatty Acids

Abstract: Lipid signaling is dysregulated in many diseases with vascular pathology, including cancer, diabetic retinopathy, retinopathy of prematurity, and age-related macular degeneration. We have previously demonstrated that diets enriched in ω-3 polyunsaturated fatty acids (PUFAs) effectively reduce pathological retinal neovascularization in a mouse model of oxygen-induced retinopathy, in part through metabolic products that suppress microglialderived tumor necrosis factor–α. To better understand the protective effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
219
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 222 publications
(224 citation statements)
references
References 62 publications
3
219
1
1
Order By: Relevance
“…a (Kabara et al, 1972;Hallahan and Garland, 2005;Desbois et al, 2008;Lafourcade et al, 2011;Sapieha et al, 2011;Valenzuela et al, 2012;Hamilton et al, 2015;Jiang et al, 2016). b (d'ippolito et al, 2015).…”
Section: Lipids and Fatty Acids In Diatomsmentioning
confidence: 99%
See 1 more Smart Citation
“…a (Kabara et al, 1972;Hallahan and Garland, 2005;Desbois et al, 2008;Lafourcade et al, 2011;Sapieha et al, 2011;Valenzuela et al, 2012;Hamilton et al, 2015;Jiang et al, 2016). b (d'ippolito et al, 2015).…”
Section: Lipids and Fatty Acids In Diatomsmentioning
confidence: 99%
“…Omega-3 fatty acids such as EPA and DHA have been found to have effects in alleviating a number of health conditions (e.g., arteriosclerosis, hypertension, inflammation, microbial, viral, and tumor activity). EPA and DHA play important roles in protecting cardiovascular system (Sapieha et al, 2011), vision (Hallahan and Garland, 2005), and treating psychiatric disorders (Lafourcade et al, 2011).…”
Section: Fatty Acidsmentioning
confidence: 99%
“…A widely accepted theory to explain the health-promoting effects of omega-3 fatty acids is that they suppress the metabolism of omega-6 arachidonic acid (ARA) to form proangiogenic or proinflammatory eicosanoids or serve as alternative substrates to generate omega-3 lipid mediators with beneficial actions (9). Indeed, the metabolism of omega-3 fatty acids by cyclooxygenase (COX) and lipoxygenase (LOX) enzymes generates 3-series prostaglandins (10,11) and leukotrienes (12), as well as unique omega-3 autacoids such as resolvins and protectins (13), which have antiinflammatory or antiangiogenic effects.…”
mentioning
confidence: 99%
“…Studies have suggested numerous benefits of omega-3 fatty acids such as prevention of cardiovascular diseases, inflammation, allergies, hypertension, arthritis, some cancers, and multiple sclerosis among others (LIMA et al, 2007;RUIZ-RODRIGUEZ;REGLERO;IBAÑEZ, 2010;SAPIEHA et al, 2011).…”
mentioning
confidence: 99%